DESCRIPTIVE STUDY OF BLOOD PRESSURE BASED ON PHYSICAL ACTIVITY AND FAST FOOD EATING BEHAVIOR IN SECOND YEAR FEMALE STUDENTS OF THE HEALTH FACULTY OF MUHAMMADIYAH UNIVERSITY OF GRESIK - Dewi, Made Sawitri; Ariestiningsih, Eka Srirahayu; Supriatiningrum, Dwi Novri (Universitas Muhammadiyah Gresik, 2024)
The objective of this study is to determine the blood pressure based on physical activity and fast food eating behavior among female students level II at the Faculty of Health, Universitas Muhammadiyah Gresik. This research was conducted through quantitative descriptive observational methods in March and July 2023. The subjects in this research were level II female students who were selected using a cluster random sampling technique. The results of this study show that (1) the frequency of eating fast food for pre-hypertension and normal blood pressure is mostly rare, namely 90.9% and 68.8%. (2) Most types of fast food eating at normal blood pressure and pre-hypertension are in the high sugar category, namely 68.8% and 84.5%. (3) The energy intake of those with normal blood pressure was mostly normal (27.3%), the energy intake of those with pre- hypertensive blood pressure was mostly a severe deficit and normal (36.4%). (4) Protein intake for those with normal blood pressure is mostly excessive (32.5%). Protein intake for those with pre-hypertensive blood pressure is mostly a severe deficit (36.4%) (5) Fat intake for those with normal blood pressure is mostly excessive (44.2%), fat intake for those with pre-hypertensive blood pressure is mostly severe and mild deficits (36.4%). (6) Carbohydrate intake for those with normal blood pressure was mostly normal (39.0%), carbohydrate intake for those with pre-hypertensive blood pressure was mostly normal (36.4%).